Analyses of different processes governing soil erosion by water in the tropics - Lal, R. (International Association of Hydrological Sciences, 1981)
Soil erosion hazard in tropical Africa is a serious threat towards sustained productivity. The available basic research information on soil, climate, and land use is rather sketchy and indicates that the severity of the erosion hazard may be attributed to soil characteristics, low soil loss tolerance, and climatic factors that lead to accelerated soil erosion following a change in land use. Researchers in the tropics have yet to establish appropriate methods for monitoring and estimating, precisely and by simple techniques, soil erodibility and erosivity in relation to soil and rainfall characteristics. There is a little information on the soil loss tolerance or acceptable levels of soil loss.